ENGLISH- OVERVIEW OF IMPACTS OF TECHNOLOGY AND DIGITALIZATION ON FAMILY DYNAMICS: AN ISLAMIC PERSPECTIVE - Aqsa Tasgheer; Asma Shahid (دی اسکالر)
Technology and Digitalization have greatly influenced family systems and culture. Familial values and socialization approaches are also shifting for the past few decades due to communication media. Latest technologies and digital advancement have manifold and diverse effects on marital relations and familial interactions. Nevertheless, it is still an issue of debate whether the power of this digital advancement and its widespread accessibility has constructive or destructive outcomes in various aspects of family life. This paper will investigate the evolving patterns in which families engage as a consequence of recent technological development. Pakistani families, in particular, will be observed in this regard. Islam is a complete code of life furnishing patterns for ideal family life. In this research paper strategies and foundations for shaping digital transformation from a family viewpoint and Islamic perspective will be studied. In the end, recommendations will be given that how digital encroachment can be advantageous to boost family dynamics.